Analisis Faktor Yang Menyebabkan Rendahnya Cakupan Imunisasi Hepatitis B di Wilayah Kerja Puskesmas Hutaimbaru Kabupaten Padang Lawas Utara - Nursia Harahap; Mappeaty Nyorong; Achmad Rifai (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2021)
Hepatitis B vaccine is mandatory for every child. The purpose of this study was to determine what factors caused the low coverage of hepatitis B immunization in the working area of ​​the Hutaimbaru Public Health, North Padang Lawas Regency. The design of this study used an analytic survey with a cross sectional study design. The sample in this study were mothers who had children under five in the working area of ​​the Hutaimbaru Public Health, North Padang Lawas Regency, namely 50 mothers who had toddlers who were obtained using purposive sampling technique. Data collection was carried out using a questionnaire. Data were analyzed using chi-square statistics and logistic regression. The results showed that there were influences of knowledge, culture, ease of access, husband's support, equipment and health promotion, religious leaders, health workers and the low coverage of Hepatitis B immunization in the Hutaimbaru Health Center, Padang Lawas Utara Regency. The variable that is most associated with the low coverage of Hepatitis B immunization in the Hutaimbaru Public Health, North Padang Lawas Regency is the support variable of religious leaders. The suggestion in this research is that it needs research on local people's perceptions about certain immunizations or vaccines. Identification of local issues and key influencers is important to increase confidence in the immunization program.